KAJIAN STILISTIKA NOVEL HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Hadi Siswanto (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The purpose of stylistics analysis of Laskar Hujan Bulan Juni was an analysis of language usage of that novel. This descriptive-qualitative research aimed at describing the unique word choice and the use of word, the special aspect of morphology, and syntax, the use of figurative language consisted of idiom, figurative sense, connotative, metaphor, metonymy, simile, personification, and hyperbole in Hujan Bulan Juni novel. The data of this research were lingual language data that contained the unique of the vocabulary, morphosyntax and the unique of figurative language. The techniques in data were taken with literary, observation, written techniques. Analysis technique used was flowing analysis concisted of three activities; data reduction, presenting data and taking a cunclusion. This study used distributional method, that was explained by substitution technique and delition technique. The results of the research showed that the unique choice and use of word was foreign language lexicon, Javanese lexicon, science lexicon, greeting word, conotative word in the title.